Experiencing architecture in the nineteenth century : buildings and society in the modern age - Gillin, Edward John, 1990-; Joyce, H. Horatio (Bloomsbury Academic, 2019)
Bringing together fourteen original essays, this collection opens up new perspectives on the architectural history of the nineteenth century by examining the buildings of the period through the lens of 'experience'. With a focus on the experience of the ordinary building user - rather than simply on the intentions of the designer - the book shows that new and important insights can be brought to our understanding of Victorian architecture. The chapters present a range of ideas and new research - some examining individual building case studies (from grand hotels and clubhouses in New York to the parliament buildings of Westminster), and others exploring conceptual questions about the nature of architectural experience, whether sensory or otherwise. Yet they share the premise that the idea of the 'experience of architecture' took on a new and particular significance with the rise of industrial modernity, and they examine what contemporary people - both architects and non-architects - understood by this idea. The insights in this volume extend beyond the study of Victorian architecture. Together they suggest how 'experience' might be used as a framework to produce a more convincingly historical account of the artefacts of architectural history.
Keywords: Architecture and society -- History -- 19th century.; Architecture -- Psychological aspects.; elektronické knihy; electronic books